Sleep Quality Profile of a group of Medical Students (Research, Society and Development, 2020)
Introduction: Admission to a university generates major impacts on the lives of medical students, as the change in routine and the new level of charge, due to the responsibility of the future profession, can impact health and sleep quality. Objective: To evaluate the quantity and quality of sleep of medical students at the Federal University of Alfenas. Methodology: Medical students were included in the sample, who answered three data collection instruments: I) Sociodemographic Questionnaire; II) Epworth Sleepiness Scale; and III) Pittsburgh Sleep Quality Index, which were applied by the researchers both at the beginning and at the end of the second and third periods of the course, totaling four surveys. Results: There was a decrease in the number of hours of sleep per night and an increase in daytime sleepiness during the period of classes, with intensification of the problem in the questionnaires referring to the end of the school semester. Conclusion: The students showed worse quality and quantity of sleep when compared to the beginning and the end of the academic semesters.